To find the cost of the drink, we can set up the equation based on the information given:
The cost of a slice of pizza is \(3.19\) and the total cost of a slice of pizza and a drink together is \(5.61\).
So, the equation can be written as:
\[ 3.19 + x = 5.61 \]
Now, to solve for \(x\), we will subtract \(3.19\) from both sides of the equation:
\[ x = 5.61 - 3.19 \]
Now, perform the subtraction:
\[ x = 2.42 \]
So we can fill in the blanks in your statements:
- \( z + 3.19 = 5.61 \)
- \( x = 2.42 \)
Thus, the cost of a drink \(x\) is \(2.42\) dollars.